2015
DOI: 10.1155/2015/571782
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Xpert MTB/RIF Assay and the Conventional Sputum Microscopy in DetectingMycobacterium tuberculosisin Northern Thailand

Abstract: Background. Despite low sensitivity in detection of Mycobacterium tuberculosis, sputum acid-fast smear remains the main diagnostic method. This study aimed to compare the diagnostic performance of Xpert MTB/RIF assay versus conventional sputum acid-fast smear. Materials and Methods. A cross-sectional study was conducted at Chiang Mai University Hospital, Thailand. Patients who were ≥15 years old and had clinically suspected pulmonary tuberculosis were included. Results. 109 specimens from 57 patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
36
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 17 publications
9
36
5
1
Order By: Relevance
“…Our results are compatible with those of these previous studies; the sensitivity of Xpert assay to detect M. tuberculosis was 96.4% in acid-fast positive sputum specimens. Results similar to those in our study were obtained in Saudi Arabia, Pakistan, Thailand, and Turkey [16][17][18][19]. Our study and other studies all confirm that positive acid-fast smear correlated well with Xpert assay and TB culture.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are compatible with those of these previous studies; the sensitivity of Xpert assay to detect M. tuberculosis was 96.4% in acid-fast positive sputum specimens. Results similar to those in our study were obtained in Saudi Arabia, Pakistan, Thailand, and Turkey [16][17][18][19]. Our study and other studies all confirm that positive acid-fast smear correlated well with Xpert assay and TB culture.…”
Section: Discussionsupporting
confidence: 91%
“…In study of Pakistan, a total 403 samples were analyzed of which some are extra pulmonary specimens. The specificity of the current study was higher compared to specificity 86.4% of study conducted in Thailand [18]. The difference might be due to small sample size (109) and the gold standard used.…”
Section: Discussioncontrasting
confidence: 66%
“…For a sample to be positive, a bacterial load of 10 4 organisms is required while as identification of TB bacilli by GeneXpert require 131CFU/ml of sample. 13,14 Studies have shown that GeneXpert increased TB detection rate by 23 to 60% among culture confirmed cases while as in our study it was 47%. Culture methods like LJ medium and liquid culture are the gold standard tests for the detection of Mycobacterium tuberculosis.…”
supporting
confidence: 47%